2013
DOI: 10.1371/journal.pone.0082735
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Is Associated with Left Ventricular Hypertrophy Independent of Serum Parathyroid Hormone in Male Cardiac Patients

Abstract: BackgroundSeveral studies have shown that serum uric acid (UA) is associated with left ventricular (LV) hypertrophy. Serum levels of parathyroid hormone (PTH), which has bbe shown to be correlated with UA, is also known to be associated with cardiac hypertrophy; however, whether the association between UA and cardiac hypertrophy is independent of PTH remains unknown.PurposeWe investigated whether the relationship between serum uric acid (UA) and LV hypertrophy is independent of intact PTH and other calcium-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
0
21
0
1
Order By: Relevance
“…Among these patients, 21 were taking a xanthine oxidase inhibitor (either allopurinol or febuxostat) and/or a uricosuric drug, respectively, and were subsequently excluded. Although we analyzed SUA data from 116 male patients in our previous paper, 14) to compare the data between female and male patients over the same study period, here we further analyzed data from 519 male patients selected by the same inclusion and exclusion criteria used for female patients. These 519 male patients included 116 patients whose data have been reported previously.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these patients, 21 were taking a xanthine oxidase inhibitor (either allopurinol or febuxostat) and/or a uricosuric drug, respectively, and were subsequently excluded. Although we analyzed SUA data from 116 male patients in our previous paper, 14) to compare the data between female and male patients over the same study period, here we further analyzed data from 519 male patients selected by the same inclusion and exclusion criteria used for female patients. These 519 male patients included 116 patients whose data have been reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…These 519 male patients included 116 patients whose data have been reported previously. 14) Laboratory analysis: Blood samples were collected in the morning under fasting conditions at the time of admission as a general rule. Aliquots of serum and plasma were obtained and stored at -80°C degrees immediately until use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that coronary artery calcification (CAC) can be used as a surrogate marker of the total burden of coronary atherosclerosis and that the presence of CAC is associated with peripheral isch-"serum albumin"), and designated as corrected calcium (cCa). The measurement of FGF23 and -Klotho was performed using enzyme immunoassay kits as described elsewhere 7,24) . The eGFR was calculated by the following Modification of Diet in Renal Disease equation modified for Japanese subjects: eGFR 194 (serum creatinine) 1.094 (age) 0.…”
Section: Introductionmentioning
confidence: 99%